Black Quotidian - Delmont, Matthew F. (Stanford University Press, 2024)
Black Quotidian explores everyday lives of African Americans in the twentieth century. Drawing on an archive of digitized African-American newspapers, Matthew F. Delmont guides readers through a wealth of primary resources that reveal how the Black press popularized African-American history and valued the lives of both famous and ordinary Black people. Claiming the right of Black people to experience and enjoy the mundane aspects of daily life has taken on a renewed resonance in the era of Black Lives Matter, an era marked by quotidian violence, fear, and mourning. Framed by introductory chapters on the history of Black newspapers, a trove of short posts on individual newspaper stories brings the rich archive of African-American newspapers to life, giving readers access to a variety of media objects, including videos, photographs, and music. By presenting this layer as a blog with 365 daily entries, the author offers a critique of Black History Month as a limiting initiative and emphasizes the need to explore beyond the iconic figures and moments that have come to stand in for the complexity of African-American history. Themes highlighted include, among others, civil rights, arts, sports, politics, and women's lives. As a work of digital history, Black Quotidian models an innovative approach to research exploration and scholarly communication. As a teaching resource, it fosters self-driven exploration of primary resources within and beyond the curriculum.